2013
DOI: 10.1007/s11095-013-1107-3
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Lipid-Based Oral Drug Delivery Systems into Solid Dosage Forms: An Overview of Solid Carriers, Physicochemical Properties, and Biopharmaceutical Performance

Abstract: The diversity of lipid excipients available commercially has enabled versatile formulation design of lipid-based drug delivery systems for enhancing the oral absorption of poorly water-soluble drugs, such as emulsions, microemulsions, micelles, liposomes, niosomes and various self-emulsifying systems. The transformation of liquid lipid-based systems into solid dosage forms has been investigated for several decades, and has recently become a core subject of pharmaceutical research as solidification is regarded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(101 citation statements)
references
References 107 publications
1
98
0
2
Order By: Relevance
“…Although several studies have shown that adsorbed LBFs can increase the oral bioavailability of poorly water‐soluble drugs, a previous study has shown that these adsorbed LBFs may still underperform relative to their liquid variants . The aim of the present study was to determine whether this phenomenon of incomplete desorption of LBF from a mesoporous adsorbent (Neusilin®) is a general effect that is applicable to a range of different drugs and LBF compositions and different simulated gastrointestinal conditions.…”
Section: Discussionmentioning
confidence: 90%
“…Although several studies have shown that adsorbed LBFs can increase the oral bioavailability of poorly water‐soluble drugs, a previous study has shown that these adsorbed LBFs may still underperform relative to their liquid variants . The aim of the present study was to determine whether this phenomenon of incomplete desorption of LBF from a mesoporous adsorbent (Neusilin®) is a general effect that is applicable to a range of different drugs and LBF compositions and different simulated gastrointestinal conditions.…”
Section: Discussionmentioning
confidence: 90%
“…The SEM images of solid carriers (silicon dioxide and anhydrous calcium hydrogen phosphate) and solid SEDS loaded astaxanthin are presented in Figure . It can be seen that they have large specific surface area with excellent sorption capacity . Figure A showed that the Silicon dioxide appeared to be spherical shaped with a lot of small opening on the surface.…”
Section: Resultsmentioning
confidence: 96%
“…Pre-dissolving the drugs in the blend of lipidic and emulsifying excipients omits the disintegration/dissolution steps, which are potential ratelimiting factors for oral absorption of poorly water-soluble drugs (Wu et al, 2006;Mu et al, 2013). Solid SNEDDS (S-SNEDDS) are relatively more recent technological modifications considered to be most sought after over the liquid SNEDDS, plausibly due to higher drug loading, better portability, improved stability and above all higher patient compliance (Bansal et al, 2008;Tan et al, 2013). Till date, most literature reports available on S-SNEDDS demonstrates the additional use of solidifying excipients including inert porous carriers, adsorbents, polymers along with equipmentintensive techniques like wet granulation, melt extrusion, extrusion-spheronization and spray drying for transformation of liquid SNEDDS into S-SNEDDS (Tang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%